Improving Students’ Literation Through The Implementation of Mind Mapping Based Discovery Learning Model - Khoiriah, Khoiriah (Jurnal Pendidikan MIPA, 2019)
This study aims to apply the discovery learning model based on concept maps to improve student literacy. As many as 25 students of class VIIIF SMPN 16, were chosen as the research sample. Literacy ability is measured by observation using an observation sheet with regard to student attitudes when discovery through reading activities. Students' responses to learning are also measured through focus group interview (FGI). The results showed that the application of this model could improve the literacy culture of students with a score of 74.67 and the average student learning outcomes obtained a score of 81.53 which included good categories.Keywords: discovery learning, mind mapping, literacy. DOI: https://dx.doi.org/10.23960/jpmipa/v20i1.pp12-16